1984
DOI: 10.1017/s0081305200016769
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Increasing Panama Canal Toll Rates on U.S. Grain Exports

Abstract: Some believe Panama Canal toll rates will increase dramatically as Panama's sovereignty over the Canal becomes complete at the end of this century. This paper focuses on the ability of Panama Canal management to extract additional toll revenues from United States grain traversing the Canal and the impact of increased toll rates on export grain flows. Analyses show toll rates established by a revenue-maximizing Canal management would exceed historical and current rates. A monopolizing Canal operator would have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Also, there are works projecting grains and dry bulk cargo with an expanded Canal including Informa Economics (2011) and Nathan Associates (2012), the latter including the growing production and export of grains through the PNW, but neither study estimated an explicit demand equation for grains/soybean. Pertaining to the competitiveness of the waterway and the importance of Canal's transit cost, Fuller et al (1984) developed a spatial model to test Panama Canal toll rate increases on U.S. grains exports through the U.S. Gulf to Asia and West Coast of Central and South America, assuming a revenue-maximizing Panama Canal administration. This study revealed a relatively inelastic link between U.S. grain flows through the waterway and toll rates, and highlighted the impact of ocean freight rate and port costs between U.S. Gulf versus U.S. PNW grain flows.…”
Section: Literary Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, there are works projecting grains and dry bulk cargo with an expanded Canal including Informa Economics (2011) and Nathan Associates (2012), the latter including the growing production and export of grains through the PNW, but neither study estimated an explicit demand equation for grains/soybean. Pertaining to the competitiveness of the waterway and the importance of Canal's transit cost, Fuller et al (1984) developed a spatial model to test Panama Canal toll rate increases on U.S. grains exports through the U.S. Gulf to Asia and West Coast of Central and South America, assuming a revenue-maximizing Panama Canal administration. This study revealed a relatively inelastic link between U.S. grain flows through the waterway and toll rates, and highlighted the impact of ocean freight rate and port costs between U.S. Gulf versus U.S. PNW grain flows.…”
Section: Literary Reviewmentioning
confidence: 99%
“…Also, as part of the interport competition between the U.S. Gulf exports versus PNW, we are including in our model U.S. Gulf -Japan and PNW-Japan freight rate differentials or freight rate spread as predictors because of the relevance of ocean transportation cost. Harris (1983) explained that ocean freight rates are part of the landed cost of grains at destination and Fuller et al (1984) assumed that Panama Canal tolls are incorporated into ship costs and are, thus, included in ocean shipping rates for the routes involving the waterway. Thus, as the ocean freight rate spread between the U.S. Gulf versus PNW increases, that is, the cost of transporting soybeans from the U.S. Gulf to Japan increases relative to the PNW to Japan, we should expect fewer soybean flows through the Panama Canal.…”
Section: Hypotheses and Research Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In atypical reports for shipping economists, Binkley and Harrer (1981) and Park and Koo (2000) descend the geographical scale and get involved with individual routes in explaining the rate structure to US trading partners. Fuller et al (1984), Koo et al (1988) and Viscencio-Brambilla andFuller (1986, 1987) evaluate the effects that changes in ocean freight rates, port and canal charges, and channel depths might have on US grain exports, at home and abroad. Kavussanos (1996) estimates bilateral export price elasticities for dry bulk cargo between 30 trading regions worldwide.…”
Section: Introductionmentioning
confidence: 99%